Vincent van Gogh an explosion of colours. (distributed by Britannica Encyclopaedia Educational Corporation, 1989)
Based on the correspondence between van Gogh and his family and friends - especially his brother Theo van Gogh, a gallery owner - this program focuses on Vincent's final years.